INITIATION RESPONSE FEEDBACK (IRF) TECHNIQUE IN CLASSROOM INTERACTION - Rafika Dewi Nasution (BAHAS, 2020)
Abstrak This study aims to analyze the types of IRF (Initiation-Response-Feedback) technique that used by the teacher and students in classroom interaction based on Sinclair and Coulthard. The most dominant structure of IRF is teacher elicit (IRF) that produced by the teacher who is expected to create classroom interaction. The reason of the most dominant structured occurred in classroom interaction because the teacher always stimulated the students by questioning and ordering. This study is expected to be an inspiration for other researchers to conduct more conductive research in the future about Initiation Response Feedback (IRF) technique in classroom interaction.   Keywords: Initiation Response Feedback (IRF), Classroom Interaction, Speaking.